2017
DOI: 10.11648/j.jddmc.20170304.12
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents, Biological Activities, Therapeutic Potentials and Nutritional Values of <i>Moringa oleifera</i> (Zogale): A Review

Abstract: Abstract:Moringa oleifera popularly known as Zogale in Northern Nigeria is one of the most widely distributed and cultivated plant species in the region. Moringa oleifera is a small or middle-sized tree, about 10m in height and is cultivated for different purposes such as vegetable, spice, medicine, for cooking and cosmetic oil. Different parts of this plant contain a profile of important minerals, and are a good source of protein, vitamins, β-carotene, amino acids and various phenolics. It was reported that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…Furthermore, it is widely cultivated due to its high adaptability to environmental conditions (1,2). M. oleifera seed oil is a sustainable source of renewable energy for biodiesel production (3) due to its high content of monounsaturated fatty acids (4). There are enormous efforts to spread the use and cultivation of M. oleifera in many countries since it is a significant source of fats, proteins, β-carotene, vitamin C, iron, potassium and other nutrients with low toxicity of seeds and leaves (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is widely cultivated due to its high adaptability to environmental conditions (1,2). M. oleifera seed oil is a sustainable source of renewable energy for biodiesel production (3) due to its high content of monounsaturated fatty acids (4). There are enormous efforts to spread the use and cultivation of M. oleifera in many countries since it is a significant source of fats, proteins, β-carotene, vitamin C, iron, potassium and other nutrients with low toxicity of seeds and leaves (5).…”
Section: Introductionmentioning
confidence: 99%
“…C, vit. A (Beta-carotene)), amino acids and fatty acids like linoleic, linolenic, and behenic acid (Maizuwo et al, 2017). It contains large amounts of various phytochemicals including phenolics, tannins, saponin, glucosinolates, flavonoids, flavonol glycosides, quercetin, kaempferol, phytate, and lectins (Maizuwo et al, 2017;Atta et al, 2017;.…”
mentioning
confidence: 99%
“…A (Beta-carotene)), amino acids and fatty acids like linoleic, linolenic, and behenic acid (Maizuwo et al, 2017). It contains large amounts of various phytochemicals including phenolics, tannins, saponin, glucosinolates, flavonoids, flavonol glycosides, quercetin, kaempferol, phytate, and lectins (Maizuwo et al, 2017;Atta et al, 2017;. These phytochemicals help in treating various diseases as antidiarrheal, antiulcerative, and hepato-and nephroprotective, antidiabetic and anticancer effects (Gopalakrishnan et al, 2016;Shalaby et al, 2016;Atta et al, 2017Atta et al, , 2018Villarruel-López et al, 2018;Hagoel et al, 2019).…”
mentioning
confidence: 99%
“…In this context, Moringa oleifera is a tree native to India that grows in tropical and subtropical regions of Africa, Asia and the Americas. This plant represents a very effective natural agent used for water purification [13]. Previous data acquired by our research group indicated that roots of M. oleifera have an elevated peroxidase activity.…”
Section: Introductionmentioning
confidence: 99%